2011
DOI: 10.1002/for.1174
|View full text |Cite
|
Sign up to set email alerts
|

New proposals for the quantification of qualitative survey data

Abstract: In this paper we deal with several issues related to the quantification of business surveys. In particular, we propose and compare new ways of scoring the ordinal responses concerning the qualitative assessment of the state of the economy, such as the spectral envelope and cumulative logit unobserved components models, and investigate the nature of seasonality in the series. We conclude with an evaluation of the type of business cycle fluctuations that is captured by the qualitative surveys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Using the notion of spectral envelope, Proietti and Frale (2011) show that the balance statistic has a filtering role and extracts the underlying cycle imbedded in a time series of counts. Let individual 's true expectation about time period be * .…”
Section: Quantification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the notion of spectral envelope, Proietti and Frale (2011) show that the balance statistic has a filtering role and extracts the underlying cycle imbedded in a time series of counts. Let individual 's true expectation about time period be * .…”
Section: Quantification Methodsmentioning
confidence: 99%
“…8 It allows us to compare, contrast, and combine measures of inflation expectations based on both qualitative data and quantitative responses. By 5 See, among others, Fishe and Lahiri (1981), Dasgupta and Lahiri (1992), Ash et al (1998), Nardo (2003), Kakoska and Teksoz (2007), Lui et al (2011), Proietti and Frale (2011), Breitung and Schmeling (2013), Vermeuleu (2014), Lahiri and Zhao (2015), and Kaufmann and Scheufele (2017) for developments in quantification methods over the last 30 years. 6 Curtin (2007Curtin ( , 2010 and Bruine de Bruin et al (2017) document systematic differences in reported inflation expectations across several surveys in the United States and offer several rationalizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In repeated preferences and attitudes surveys an obvious extension is letting the preference and uncertainty parameters vary over time. A simple illustration is provided by the analysis of consumer opinion surveys, for which the CUB approach can provide an alternative way of quantifying the results, which typically take the form of the percentage of responses falling into ordinal categories; see also Proietti and Frale (2011).…”
Section: Time Series Extensionsmentioning
confidence: 99%